Perancangan Sistem Deteksi Banjir Berbasis IoT Untuk Peringatan Dini dengan Sistem Integrasi Web - Zharfan Maftuh Arrasyidy; Abd. Hallim; Abdul Rahim (Pusat Riset dan Inovasi Nasional, 2025)
This study presents the development of an Internet of Things (IoT)-based flood detection and early warning system designed to improve the accuracy and response time of conventional flood monitoring methods. The system integrates a water level sensor and ESP32-CAM module, managed by an ESP32-WROVER microcontroller, to monitor water levels in real time. Data is transmitted wirelessly and visualized on a web platform built with PHP and MySQL. When water levels exceed a predefined threshold, the system automatically sends alerts via the Telegram messaging app. Testing shows high precision with a margin of error under 0.3 cm and notification delivery within three seconds. The system’s ability to combine numerical data and live imagery enhances situational awareness and accessibility. Overall, the solution offers an efficient and innovative approach to flood risk mitigation using IoT technology.